The postconceptual condition: critical essays - Osborne, Peter (London Verso Books, 2018)
If, as Walter Benjamin claimed, it is the function of artistic form & to make historical content into a philosophical truth then it is the function of criticism to recover and to complete that truth. Contemporary art makes this work more difficult than ever. Todays art is a point of condensation for a vast array of social and historical forces, economic and political forms, and technologies of image production. Contemporary art, Osborne maintains, expresses this condition through its distinctively postconceptual form. These essaysextending the scope and arguments of Osbornes Anywhere or Not At All: Philosophy of Contemporary Artmove from a philosophical consideration of the changing temporal conditions of capitalist modernity, via problems of formalism, the politics of art and the changing shape of art institutions, to interpretation and analysis of particular works by Akram Zaatari, Xavier Le Roy and Ilya Kabakov, and the postconceptual situation of a crisis-ridden New Music.